Foreign exchange hedge for fdi in infrastructure projects - Santos Filho, Jorge Ferreira dos (2023)
The main objective of this doctoral dissertation is to study the relationship between foreign direct investments (FDI) x public-private partnerships (PPP) x exchange rate protection (FEH) in infrastructure projects. For this, the doctoral thesis is structured in three articles, being 2 systematic reviews and 1 qualitative study. Article I is systematic literature review about Project Finance, FDI and PPP. The results indicate that the literature is already consolidated, however there are knowledge gaps, especially regarding their behavior in relation to government policies in emerging economies. Article II presents a systematic literature review on Foreign Exchange Hedge, indicating that the markets, despite the classic division in developed and developing countries, tends to be divided in three main groups related to their relationship with the US market, proposing the following new classification: (i) the US market; (ii) large markets; and (iii) small and medium markets. The study also found that the market opportunities and constraints on the risks are the main motivations of the studies on foreign exchange hedge in the contemporary context of the global financial market. Article III presents a qualitative study indicating crucial points related to exchange rate risk in FDI applied in infrastructure projects using PPP in the Brazilian context and how the exchange rate risks impact the decisions of the economic actors involved in FDI operations applied in PPP infrastructure projects in Brazilian context; and the differences between protection mechanisms used by the public (bidders and government representatives) and private (investors and financiers) sectors against the exchange rate risks in financing operations for PPP infrastructure projects in developing countries.